Traitement tertiaere d'un effluent domestique secondaire par culture intensive de la cyanobactérie phormidium bohneri: Tertiary treatment of secondarily treated urban wastewater by intensive culture of phormidium bohneri - Proulx, Daniel; Lessard, Paul; De La Noüe, Joël (My University, 1994)
Phormidium bohneri, a self-flocculating cyanobacterium, was grown outdoors in a 75 1 intensive culture basin (semi-continuous system) and used for the tertiary treatment of domestic wastewater. The behavior, growth and purification potential of P. bohneri were studied. The nutrient removal efficiency (max.: Ni = 83%, 12.5 mgN l-1 d-1; Pi =81%, 1.3 mg P L-1 d-1) of this process allows a quite rapid treatment of the secondary effluent (hydraulic retention time=1d). Stripping account for about 62% of nitrogen (NH3) removal while 38% is assimilated by P. bohneri. Inorganic phosphorus is removed mainly by precipitation (57%) and to a lesser extent is taken-up by Phormidium (43%). The cyanobacterial biomass (P: 1.1%, N: 8.6%, protein: 53.5%, dry weight basis) can be easily harvested after the treatment by settling. © 1989 Taylor and Francis Group, LLC.
Keywords: Cyanobacteria; Domestic wastewater; Phormidium bohneri; Solar biotechnology; Tertiary treatment